Unusual Presentation of COVID 19 - A Case report - tuli, Tasmina Chowdhury; halima, Sadia; ava, Arfa Rahman; islam, Quazi Tarikul (Bangladesh Journal of Medicine, 2020)
An acute respiratory disease caused by a new strand of coronavirus (SARS-CoV-2), which was ûrstidentiûed in Wuhan, Hubei Province, China, quickly developed into a global pandemic. Commonpresentation associated with corona-virus disease 2019 (COVID-19) include fever, cough, and lesscommonly diarrhea, sore throat, chest pain, nausea, and vomiting , loss or attenuation of smell andtaste sensation and palpitations. Till now observed sequelae are ARDS, multi organ dysfunction,thrombotic events and coagulation disorder, myocarditis .With time clinicians are observing emergenceof new and unusual presentation, complications and sequelae of the disease. Our case report is of amiddle aged man with typical symptoms of COVID 19 who ultimately developed right sided tensionpneumothorax. Along with O2 therapy, anticoagulant, anti inflammatory drugs and other supportivetreatment he was managed with water seal drainage. Though till date COVID 19 is not very wellknown to us but development of tension Pneumothorax as asequelae is atypical as far observedwhich made this case interesting. Bangladesh J Medicine July 2020; 31(2) :102-106